Existing Legislative Solutions and Prospects for Improving the Quality of Atmospheric Air in Poland in Relation to the European Union Requirements for the Reduction of Harmful Emissions to the Atmosphere Planned for 2030 - Przemyslaw SZOPA (Communications of International Proceedings, 2021)
Atmospheric air as a component of the natural environment requires protection and improvement of quality, which is important for the multifaceted policy of sustainable development of countries. In particular, Poland has to restructure, in the coming years, many branches of the economy, which are still largely based on the use of energy from hard coal processing. The article discusses issues related to the introduced solutions aimed at reducing greenhouse gases emission into the atmosphere by the Polish state. An analysis of the most important legal acts adopted by Polish governments taking into account the European Union low-emission guidelines over the last 20 years was carried out. Present solutions at the national and local level are presented, which in the near future give rise to the assumption that Poland, as a member state of the European Union, will be able to significantly reduce harmful emissions into the air in terms of emission indices assumed and approved for the member states by the European Commission for 2030.
Keywords: Ambient (atmospheric) air quality; emission management; low emission; sustainable development